Pengaplikasian Metode Activity Based Costing Pada Perhitungan Unit Cost di Pelayanan Kesehatan Gigi dan Mulut - Rika Irma Yanti; Febrian Febrian; Desy Purnama Sari (Andalas Dental Journal, 2019)
Dental clinic is one type of privateowned service enterprise providing dental and oral health services. In the current global era, dental clinics must be able to compete with other dental health facilities. Dental clinics are required to manage effectively clinical management, especially in financial accounting. Unit cost calculation using Activity Based Costing (ABC) method is a modern calculation. It has been implemented in several health facilities. The basic concept of ABC is a product derived from activities that will consume costs. The purpose of this paper is to provide an overview of the application of unit cost calculations with ABC in dental clinics. So it can formulated four steps of unit cost calculation with ABC as follows: preparation of data collection, data collection, ABC calculation of the first stage, ABC calculation of the second stage. The results of the calculation of unit cost with ABC are clinical financial accounting data which are used as a consideration in making desicion of the clinical strategy.